Imperfect competition in the banking sector and economic instability - Carli, Francesco (2024)
We study the impact of competition in the banking sector on the emergence of endogenous cycles driven by self-fulling volatile expectations. We consider an OLG model with two sectors and two household types: workers, who consume and work when young and save through bank deposits; and entrepreneurs, who seek bank loans to finance current consumption and to invest in a productive technology that transforms the consumption good into capital. When old, entrepreneurs rent this capital to firms, who produce the consumption good using capital and labor. All markets are perfectly competitive, except the loans market where banks compete à la Cournot under free entry and exit. In the absence of externalities in the capital producing technology, more competition in the banking sector promotes the emergence of local indeterminacy and sunspots fluctuations. In contrast, under constant social returns to scale in the capital producing technology, bank market power alone triggers the emergence of local indeterminacy. With increasing social returns to scale, both market power and externalities facilitate the emergence of local indeterminacy. Additionally, when banks have market power, steady state multiplicity may emerge, opening the way to global indeterminacy and fluctuations.